THE DEVELOPMENT AND ANALYSIS OF PAI TEACHER RESOURCES - Ali Ridho; Ernaka Heri Putra Suharyanto; Junaidi Junaidi (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2020)
AbstractThis study discusses the development and analysis of PAI teacher resources related to several competencies that PAI teachers must have so that they are more in line with the needs of students who learn about Islamic teachings through a well-planned or programmed learning process. In addition, prospective PAI teachers also need to be selected to match the background of the department or study program of Islamic education.The method of discourse and content analysis is used in this paper, by discussing a number of literatures and then analyzing them analytically based on the objectives and developments of the study of PAI Teacher Resources on some aspects of education in general.